Beyond Traditional Practicums: Exploring the Potential of Scalable Practicum in Science Courses - Kusmawan, Udan (Studies in Learning and Teaching, 2024)
Initiated during the Covid-19 pandemic, this study examines the development and use of virtual laboratories at 'Universitas Terbuka' to facilitate science practicums. Initially a response to pandemic restrictions, these virtual labs proved to be invaluable due to the widespread geographic distribution of students across the Indonesian archipelago. As the world transitions to a new normal, with possibilities for on-site practical experiences resuming, this paper discusses how virtual labs can continue to ensure equitable access to practical science education. This aspect of equal opportunity in education, whether online or on-site, is termed 'scalable practicum' in this study. By using a combination of qualitative and quantitative research methods, the paper evaluates the effectiveness of these virtual labs in providing hands-on scientific experimentation experiences that are both accessible and flexible. The findings suggest that, even beyond pandemic constraints, virtual labs remain a feasible and efficient alternative to traditional in-person labs, significantly enhancing student engagement and learning outcomes. This paper emphasizes the adaptability of virtual labs to various learning contexts and their importance in the evolving landscape of science education. The study concludes by recommending further research with a broader demographic to thoroughly evaluate the long-term viability and impact of online scalable practicums in science learning.